1990
DOI: 10.1159/000146825
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of the Mongolian Gerbil Uterus

Abstract: The postnatal development of the gerbil uterus has been investigated. Special attention has been paid to the luminal surface epithelium. In the newborn gerbil, the uterus contains already some fluid and the uterine luminal epithelium seems to possess mechanisms for the regulation of the fluid contents. Among them are apical protrusions and microvilli, endo- and exocytotic vesicles of different nature, highly active Golgi complexes and dilated rER vesicles and also very distinct junctional complexes between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…4,6). There are hardly any of the heteromorphic protrusions as described by Kress and Mardi (1990a) for the uterine luminal cells (Fig. 5).…”
Section: Day 1 Pnmentioning
confidence: 80%
“…4,6). There are hardly any of the heteromorphic protrusions as described by Kress and Mardi (1990a) for the uterine luminal cells (Fig. 5).…”
Section: Day 1 Pnmentioning
confidence: 80%
“…Experiments have shown that rising levels of estrogen suppress the formation of solitary cilia in the uteri (Tachi, 1984). Solitary cilia have been found in the uteri during postnatal development in mice (Plapinger, 1982) or Mongolian gerbils (Kress & Mardi, 1990). They disappeared at sexual maturity, in eutheria, solitary cilia are rarely seen in actively cycling animals.…”
Section: Discussionmentioning
confidence: 99%
“…First attempts in this field are the studies of Bertschinger [ 1987], Kress et al [1989] and Kress and Mardi [1990]. There are no reports on work on changes in the glandular epithelium during the period of post natal development, whether in the gerbil or in rodents generally.…”
Section: Introductionmentioning
confidence: 99%